The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1159/000479818
|View full text |Cite
|
Sign up to set email alerts
|

Atypical Uterine Smooth Muscle Tumors: A Retrospective Evaluation of Clinical and Pathologic Features

Abstract: Background: Clinical characteristics combined with new biomarkers help discriminate between atypical uterine smooth muscle tumors (AUSMT) and leiomyosarcomas (LMS). Patients and Methods: We retrospectively collected a series of leiomyomas (LM), AUSMT, and LMS. Estrogen receptors (ER), progesterone receptors (PR), p16, Ki-67, and p53 expression were assessed by immunohistochemistry. For AUSMT patients, immunohistochemistry evaluations were performed at the time of diagnosis and at recurrences. Results: A total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 27 publications
2
8
0
Order By: Relevance
“…In an earlier study, Blom et al (1998), found no such link, but they did find a connection between p53 and the frequency of recurrence in LMS [84]. Similar findings were reported by Maltese et al (2018), who very recently described that ER status ( p = 0.027) and p53 expression ( p = 0.015) predicted the risk for relapse in LMS [85]. Notably, p53 positivity in the case of malignant lesions is usually spread, as opposed to focal reaction in the case of benign changes.…”
Section: Available Immunohistochemical Markerssupporting
confidence: 52%
See 1 more Smart Citation
“…In an earlier study, Blom et al (1998), found no such link, but they did find a connection between p53 and the frequency of recurrence in LMS [84]. Similar findings were reported by Maltese et al (2018), who very recently described that ER status ( p = 0.027) and p53 expression ( p = 0.015) predicted the risk for relapse in LMS [85]. Notably, p53 positivity in the case of malignant lesions is usually spread, as opposed to focal reaction in the case of benign changes.…”
Section: Available Immunohistochemical Markerssupporting
confidence: 52%
“…The literature offers numerous publications about studies on ERs and PRs expressions in tissues derived from uterine smooth muscle cells [22,69,72,74,85,94,143]. ER and PR are confirmed in most cases of LMs, and various authors have confirmed different expression of ER and PR receptors in other mesenchymal tumors of the uterine body [13,17,18,85]. The number of publications on the presence of the aforementioned markers in LMS remains limited but, so far, the results presented have been consistent and confirmed decreased ER and PR receptor expression in LMS cells.…”
Section: Available Immunohistochemical Markersmentioning
confidence: 99%
“…We observed that >80% of missense mutations were localized to codon 44 (89.28%), a rate higher to the reports of (Je et al, 2012) (66.6%) and (Mäkinen et al, 2011a,b) (49%) and less to the findings of Markowski et al (2012) (95.8%) but similar to those of McGuire et al study (89.5%) (Mäkinen et al, 2011a, 2014a,b; McGuire et al, 2012). We identified a codon 36 missense mutation in one patient, which, was previously reported (Rieker et al, 2013; Sadeghi et al, 2016; Maltese et al, 2017). Our additional interesting observation is that 16% of our missense mutation positive leiomyoma cases had a novel mutation spectrum (at codons 38 and 55).…”
Section: Discussionsupporting
confidence: 74%
“…Specific molecular mechanisms underlying the genesis of leiomyomas have remained relatively unknown but there have been some suggestions regarding contributory role of age, race, early menarche, obesity, nulliparity, and steroid hormones in leiomyoma predisposition (Parazzini, 2006; Terry et al, 2010; Tropeano et al, 2012; Brohl et al, 2015; Stewart et al, 2017; Vercellini and Frattaruolo, 2017; Pavone et al, 2018). Cytogenetic studies have shown that 40 to 50% of leiomyomas harbor chromosomal abnormalities (Islam et al, 2013; Maltese et al, 2017). In addition to this, multiple studies have reported different types of mutations, altered expression and/or methylation status of hormone receptor genes, growth factors, repair genes, extracellular matrix genes, collagen and mitochondrial genes in uterine leiomyomas (Islam et al, 2013; Montgomery et al, 2014; Sant'anna et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Table 5, both patients with leiomyosarcoma had an expression of proteins p16 and p53 in the immunohistochemical tests, indicating that we should pay more attention to the risk of leiomyosarcoma recurrence in those patients with expression of p16 and p53. Recently, immunohistochemical stains have been suggested in several studies to identify which patients with STUMP had high recurrent risk, and those markers including epithelial growth factor receptor, p53, p16, galectin-3, MIB-1, BCL-2, Twist, estrogen receptor (ER), and progesterone receptor (PR) (20)(21)(22). As with previous publications, this study indicates that proteins p16 and p53 may be markers for recurrence of STUMP, considering the remarkable differences between the non-recurrence and recurrence groups (P = 0.001; P = 0.01).…”
Section: Discussionmentioning
confidence: 99%